2015
DOI: 10.5664/jcsm.4766
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Treatment Increases Serum Vitamin D Levels in Male Patients with Obstructive Sleep Apnea

Abstract: BRIEF SUMMARYCurrent Knowledge/Study Rationale: Vitamin D not only participates in bone metabolism and regulates calcium homeostasis, but also has pleiotropic effects, modulating numerous metabolic processes. Considering that patients with obstructive sleep apnea (OSA) suffer from vitamin D defi ciency and show high serum parathyroid hormone (PTH) levels, we tested the effects of short-term continuous positive airway pressure (CPAP) on serum vitamin D and PTH levels. Study Impact: These fi ndings suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 25 publications
5
53
1
5
Order By: Relevance
“…Additionally, Goswami and coworkers (2016) found that BMI and neck circumference could be a confounding factor in the association observed between 25OHD serum levels <20 ng/mL and some risk factors for OSA. A further study revealed that the use of continuous positive airway pressure (CPAP), the gold standard for OSA treatment, promoted increased levels of 25OHD (from 19.21 ± 9.45 ng/mL to 21.03 ± 9.50 ng/mL) ( Table 1) in men with OSA after 7 days of CPAP use (Liguori et al 2015). The CPAP therapy was also effective in increasing 25OHD serum concentrations from 16.05 ± 7.74 ng/mL to 25.73 ± 12.91 ng/mL after 1 year of treatment in both obese and non-obese OSA patients (Liguori et al 2016).…”
Section: :1mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Goswami and coworkers (2016) found that BMI and neck circumference could be a confounding factor in the association observed between 25OHD serum levels <20 ng/mL and some risk factors for OSA. A further study revealed that the use of continuous positive airway pressure (CPAP), the gold standard for OSA treatment, promoted increased levels of 25OHD (from 19.21 ± 9.45 ng/mL to 21.03 ± 9.50 ng/mL) ( Table 1) in men with OSA after 7 days of CPAP use (Liguori et al 2015). The CPAP therapy was also effective in increasing 25OHD serum concentrations from 16.05 ± 7.74 ng/mL to 25.73 ± 12.91 ng/mL after 1 year of treatment in both obese and non-obese OSA patients (Liguori et al 2016).…”
Section: :1mentioning
confidence: 99%
“…A pilot study assessing Caucasian OSA individuals submitted to cholecalciferol supplementation (4000 IU/ day) during 15 weeks (Kerley et al 2017) showed an increase in 25OHD serum levels in the supplemented group vs placebo (100.8 ± 39.9 nmol/L × 43.0 ± 21.4 nmol/L, respectively), and a decrease in metabolic parameters such as low-density lipoprotein (LDL) and lipoproteinassociated phospholipase A2 (Lp-PLA2). Some subjects from both groups used CPAP, but the data were not controlled, hampering the interpretation about the benefits of the supplementation since there is current evidence that CPAP use can increase 25OHD levels (Liguori et al 2015).…”
Section: :1mentioning
confidence: 99%
“…The apnea-hypopnia index (AHI) is defined as the ratio between the sum of all apneas (>90% reduction in airflow for >10 s) plus all hypopneas (>30% reduction in airflow >10 s) associated with ≥3% O 2 desaturation (Berry et al, 2012) and time in bed. In addition to AHI, also the following oxygen saturation (SaO 2 ) parameters were ª 2017 European Sleep Research Society measured: mean SaO 2 , lowest SaO 2 , mean SaO 2 desaturation (SaO 2 desat) and oxygen desaturation index (ODI) (number of oxygen desaturation ≥3% episodes per hour) (Liguori et al, 2015).…”
Section: Polygraphic (Pg) Testingmentioning
confidence: 99%
“…Doksan ağır OUAS'lı hastanın dahil edildiği bir çalışmada, çalış-mamızın sonuçlarına benzer şekilde OUAS'lı grupta düşük vitamin D ve yüksek PTH düzeyleri saptanmış, yedi günlük CPAP tedavisi alan erkek OUAS'lı olgularda vitamin D düzeylerinde anlamlı bir artış izlenmiştir (20). Çalışmamızda vitamin D düzeylerinin oksijen desatürasyon indeksi ve ortalama oksijen saturasyonu arasın-da anlamlı ilişki bulunması, OUAS'da uyku esnasında tekrarlayan hipoksi ataklarının vitamin D düzeyleri üzerine olumsuz etkisinin olduğunu düşündürmektedir.…”
Section: Gündüz Aşırı Uyku Hali Ile Vitamin D Düzeyi Arasında Ki Ilişunclassified